A New CMOS Fully Differential Low Noise Amplifier for Wideband Applications - Majid Takbiri; Hadi Zarei; Abolfazl Bijari (Universitas Ahmad Dahlan, 2018)
In this paper, a multi-stage fully differential low noise amplifier (LNA) has been presented for wideband applications. A common-gate input stage is used to improve the input impedance matching and linearity. A common-source stage is also used as the second stage to enhance gain and reduce noise. A shunt-shunt feedback is employed to extend bandwidth and enhance linearity. The proposed low noise amplifier has been designed and simulated using RF-TSMC 0.18 μm CMOS process technology. In frequency band of 3.5-7.5 GHz, this amplifier has a flat power gain (S21) of 16.5 ± 1.5 dB, low noise figure (NF) of 3dB, input (S11) and output (S22) return losses less than -10 dB and high linearity with input thirdorder intercept point (IIP3) of -3dBm. It’s power consumption is also less than 10 mw with low power supply voltage of 0.8v.